2017
DOI: 10.1111/dom.13113
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin and Roux‐en‐Y gastric bypass modulate insulin secretion via regulation of intra‐islet PYY

Abstract: AimsThe gut hormone peptide tyrosine tyrosine (PYY) is critical for maintaining islet integrity and restoring islet function following Roux‐en‐Y gastric bypass (RYGB). The expression of PYY and its receptors (NPYRs) in islets has been documented but not fully characterized. Modulation of islet PYY by the proteolytic enzyme dipeptidyl peptidase IV (DPP‐IV) has not been investigated and the impact of DPP‐IV inhibition on islet PYY function remains unexplored. Here we have addressed these gaps and their effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
7
26
1
Order By: Relevance
“…By infusing the Y2R-antagonist into the brain, that study may have missed important actions of PYY in the periphery. For example, PYY has been shown to stimulate GLP-1 secretion [35], and via Y1R on pancreatic β-cells, insulin secretion [43]. However, the present findings do not suggest that PYY actions through peripheral Y2R is important for the beneficial effects of RYGB.…”
Section: Discussioncontrasting
confidence: 75%
“…By infusing the Y2R-antagonist into the brain, that study may have missed important actions of PYY in the periphery. For example, PYY has been shown to stimulate GLP-1 secretion [35], and via Y1R on pancreatic β-cells, insulin secretion [43]. However, the present findings do not suggest that PYY actions through peripheral Y2R is important for the beneficial effects of RYGB.…”
Section: Discussioncontrasting
confidence: 75%
“…Total plasma PYY is a mix of PYY and the active endocrine isoform PYY , obtained by NH 2 -terminal PYY residue cleavage by dipeptidyl peptidase-4 (DPP-4) [10]. It was recently demonstrated that PYY can modulate the insulin secretory response to glucose in the pancreas and restore glucose-induced suppression of glucagon secretion [7,11]. Furthermore, PYY can improve insulin sensitivity by increasing glucose uptake in adipose tissue and muscle in rodents [12] and slowing gastric emptying [13].…”
Section: Introductionmentioning
confidence: 99%
“…39 The fact that application of PYY or DPP-IV inhibitors consistently modifies insulin response to glucose in rodent and human islets, despite their species-specific localization, suggests a common mechanism that may lie in a conserved receptor distribution. Proteomic approaches have not successfully detected NPYRs expression in islets; 40,41 however, mRNA and protein expressions have been reported both in rodent and human islets [27][28][29]33 for all NPYR subtypes but NPYR2 (which mediates the anorectic effect of PYY and is highly selective for PYY ). NPY1R expression particularly appears to be conserved and confined to beta cells, suggestive of consistency in PYY signalling and action in rodent and human islets.…”
Section: Pancreatic Py Y Can Contribute To the Regulation Of Insulin mentioning
confidence: 99%
“…In line with this, pharmacologically or genetically mediated suppression of NPY1R pathway negatively impacts islet function and glucose tolerance. In in vitro experiments, addition of the NPY1R blocker BIBP3226 abolishes the potentiating effect of sitagliptin on insulin release, 28 while activation of NPY1R (and NPY4R, NPY5R) protects mouse and human islets from cytokine-induced apoptosis and restores their glucose responsiveness. 29 In vivo studies have also demonstrated that mice lacking NPY1R either in beta cells 42 or in osteoblasts 43 have impaired glucose tolerance, thus extending the impact of NPY signalling, that could be additionally modulated by NPY and pancreatic polipeptide, on glucose homeostasis beyond pancreatic tissue regulation.…”
Section: Pancreatic Py Y Can Contribute To the Regulation Of Insulin mentioning
confidence: 99%